Paravertebral block for patients older than 80 years in one day surgery elective mastectomy - Compagnone, Christian; Schiappa, Eleonora; Bellantonio, Daniele; Ghirardi, Gianluca; Rossini, Elisabetta; Tagliaferri, Fernanda; Fanelli, Guido (Acta Biomedica Atenei Parmensis, 2014)
Paravertebral block (PVB) has been proposed as an alternative to General anaesthesia (GA) for breast surgery. It provides good operative anaesthesia, good pain control with little adverse effects. Six women older than 80 year were selected. All patients were post-operatively interviewed about the presence of pain, nausea and vomiting. All patients declared absence of pain and nausea and that they were satisfied with the procedure. The use of PVB allows elderly patients to undergo ambulatory surgery for the treatment of breast cancer with satisfaction. This technique allows a short recovery and adequate postoperative pain relief with reduced hospital costs.